2015
DOI: 10.1890/14-2326.1
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional functional trait analysis of resource exploitation in European ants

Abstract: The major factors explaining ecological variation in plants have been widely discussed over the last decade thanks to numerous studies that have examined the covariation that exists between pairs of traits. However, multivariate relationships among traits remain poorly characterized in animals. In this study, we aimed to identify the main multivariate trait dimensions that explain variance in important functional traits related to resource exploitation in ants. To this end, we created a large ant trait databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…First, the extent of phylogenetic relatedness among species in a community varies considerably; while some studies use closely related communities (e.g. ants; Retana, Arnan & Cerdá, ), others use distantly related communities (e.g. isopods and millipedes; Coulis et al ., ).…”
Section: Current Trait‐based Studies On Terrestrial Arthropodsmentioning
confidence: 99%
“…First, the extent of phylogenetic relatedness among species in a community varies considerably; while some studies use closely related communities (e.g. ants; Retana, Arnan & Cerdá, ), others use distantly related communities (e.g. isopods and millipedes; Coulis et al ., ).…”
Section: Current Trait‐based Studies On Terrestrial Arthropodsmentioning
confidence: 99%
“…Second, Cataglyphis workers are largely scavengers of sparsely dispersed food items (53), necessitating communication with nestmates only when the food item is too large to be carried alone. Third, in relatively small colony sizes, as occur in most Cataglyphis species, lone foraging is efficient enough for colony needs (12,116). The second and third factors may explain why species that live in less arid environments (e.g., the cursor group) have not reverted to mass recruitment despite the alleviation of some ecological constraints.…”
Section: Homing and Navigationmentioning
confidence: 99%
“…Among the arthropods, ants are an ideal taxonomic group for investigating relationships between morphology, traits, and assemblage structure because they (i) are abundant, comprising the dominant fraction of animal biomass in most terrestrial ecosystems (Wilson and Hölldobler, 2005), (ii) perform a range of important ecosystems functions (Del Toro et al 2012), (iii) exhibit a very large morphological diversity at very small scales (Silva and Brandão 2010), and (iv) vary in composition along environmental gradients (Gotelli and Ellison 2002). In addition, many studies have shown that ant species have specific traits that are correlated with environmental conditions (Wiescher et al 2012), macro-or microhabitat structure (Kaspari and Weiser 1999, Gibb and Parr 2010, Yates et al 2014) and resource exploitation (Retana et al 2015). Finally, recent research with stable isotopes has identified 5 morphological space occupied by temperate and tropical ant assemblages.…”
mentioning
confidence: 99%